Complications in extracorporeal shockwave lithotripsy: a cohort study. (3rd September 2017) - Wagenius, Magnus; Jakobsson, Jon; Stranne, Johan; Linder, Adam
Abstract: Objective: The aim of this study was to evaluate clinically relevant complications within 14 days after extracorporeal shockwave lithotripsy (ESWL) in a modern setting. Materials and methods: Consecutive ESWL treatments between 2009 and 2015 in Ängelholm Hospital, Sweden, were analyzed retrospectively. The primary outcome was complications in patients seeking medical attention within 14 days after ESWL. Multivariable analysis was used to adjust for confounders such as diabetes, stone size and location, and presence of a urinary stent. Results: In total, 1838 stones were treated: 1185 (64.4%) localized in the renal pelvis, and 415 (22.5%) in the upper two-thirds and 205 (11.1%) in the lower third of the ureter. Overall, 116 out of 1838 cases (6.4%) needed medical attention within 14 days after ESWL and 75 (4%) crequired hospital care. Infection was found in 44 cases (2.4%), with a positive urine culture in 33 cases. Invasive/operative interventions were performed in 41 cases (2.2%). Distal stones had a lower risk of complications ( p = 0.02) with ESWL. Diabetes ( p = 0.02), larger stones (11–20 mm, p = 0.03; 21–30 mm, p = 0.009) and a need for antiemetics during treatment ( p = 0.02) were significantly associated with an increased risk of complications. Conclusions: Few complications are associated with modern ESWL treatment. A frequency of 1 Hz should be used to reduce complications ( p = 0.025). Diabetes and larger stone size increase the risk of complications. The need for antiemetics during ESWL requires special consideration and further study. Distal stones seem to carry a lower risk of complications ( p = 0.017).